Biodegradation of Textile Dye Wastewater with the Application of Response Surface Methodology (RSM): A Factorial Design Approach - Hanapi, Nur Hanis Mohamad; Monajemi, Hadieh; Ismail, Azimah; Suhaili, Zarizal; Endut, Azizah; Juahir, Hafizan (Trends in Sciences, 2022)
The increasing demands in textile industries has created huge production of textile coloured products globally, leading to large production of textile effluent. Textile effluent is often discharged to the environment without proper treatment by the textile factories. The untreated textile effluent typically contains harmful chemicals and is hazardous to the environment, due to the toxicity of the dyes used. In this study, biological treatment is applied to the textile effluent. A 2-level full factorial design from response surface methodology (RSM) was applied to find the optimized treatment process condition for the textile wastewater degradation. Sixteen runs of experiment with 4 factors were performed; bacterial inoculum (%, v/v), temperature (℃), agitation (rpm), and pH were tested. It was observed highest decolourization obtained (91.95 % with pH 4, low concentration of bacterial inoculum (5 %), agitation speed (200 rpm) and temperature (40 ℃)) meanwhile lowest decolourization was achieved at 73.47 % with pH 10, low concentration of bacterial inoculum (5 %), agitation speed (100 rpm) and high temperature (40 ℃). It was observed that low concentration of bacterial inoculum (%, v/v) gave more favourable dye degradation and COD removal, while pH ranged from low to high in the textile dye treatment. HIGHLIGHTS Textile wastewater contributes the most in Sg. Hiliran, as textile wastewater was discharged directly into the river without proper treatment Biodegradation using a bacterial approach offers safe and costly effective treatment for the textile wastewater The application of RSM offers a practical approach in providing optimized parameters for the textile wastewater treatment